Modelling of utility-scale PV systems and effects of solar irradiance variations on voltage levels. - Montenegro, Cristian Fernando Torres (2016)
This work presents a dynamic model for utility-scale PV systems. The model is based on a centralized converter topology, which uses a voltage-sourced converter (VSC) to facilitate the exchange of energy between PV generators and the utility grid. The related control system regulates active and reactive power injected by the PV system, based on a current control strategy. Moreover, the model includes a Maximum Power Point Tracking (MPPT) scheme, implemented with the incremental conductance method. Dimensioning of the model is presented as well as simulation cases to validate its performance. Subsequently, the model was used to analyze the effect of variations in solar radiation on a test network with high penetration of photovoltaic generation. Results showed that without proper compensation of reactive power, variations in solar radiation can cause voltage fluctuations outside allowable limits. Thus, in order to mitigate these fluctuations, local control strategies were implemented to allow the exchange of reactive power between the solar farm and the utility grid. Simulations showed that the proposed strategies can mitigate voltage fluctuations at the point of common coupling, improving voltage regulation in the network.